Analysis of Layperson Tourniquet Application Using a Novel Color-Coded Device. (1st February 2016) - Goolsby, Craig; Chen, Elizabeth; Branting, Andrew; Weissbrod, Elizabeth; David, Jason; Moore, Krista; Olsen, Cara
Abstract: Objective: To determine whether a color-coded tourniquet designed for public use increases successful tourniquet application by laypeople. Methods: This was a randomized study conducted on April 25, 2015. The study occurred during the Maryland Day activity at the University of Maryland in College Park, Maryland. Investigators recruited participants with posters displayed at major crosswalks around a central testing area. A total of 157 volunteers aged 18 years or older and without prior military service or medical training were enrolled. A participant stood in front of a waist-down mannequin with an isolated leg injury while an investigator read aloud a mass causality scenario. The investigator then asked the participant to apply a tourniquet to the mannequin's leg. All participants received a 4-step illustrated just-in-time (JiT) instruction card designed to facilitate layperson tourniquet application. Test participants received a color-coded tourniquet designed for layperson use with instructions printed on the device. Control participants received a black Combat Application Tourniquet (C-A-T; Composite Resources, Rock Hill, SC). Participants were randomized in a 1:1 ratio in blocks of 50. The primary outcome was the proportion of successful tourniquet applications by those who received color-coded tourniquets compared to those who received black tourniquets. Secondary outcomes included validation of previous data analyzing layperson success with tourniquet application, time for successful placement, reasons for failed applications, and participant self-willingness and comfort using tourniquets. We also analyzed demographic data on the study population and inter-rater reliability regarding the assessment of successful tourniquet application. Results: Participants supplied with color-coded tourniquets successfully placed the device 51.38% of the time, compared to 44.71% of the time for controls using a black tourniquet (risk ratio: 1.15; 95% confidence interval: 0.83-1.59; P= 0.404). Participants' self-reported willingness to use a tourniquet rose from 40.8% before the study to 80.3% after the study ( P <0.05). Conclusions: The color-coded device did not significantly increase laypeople's proportion of successful tourniquet applications when compared with a standard black device. However, this study reproduced pilot study data showing that laypeople can successfully apply tourniquets about half the time if provided JiT instructions. Age, sex, race, income, and highest level of education were not found to impact one's ability to properly apply a tourniquet. Laypeople's willingness to apply tourniquets doubled to 80% after brief exposure to the device. These results affirm the feasibility of engaging laypeople as immediate lifesavers of trauma victims and justify further efforts to boost rates of proper application. ( Disaster Med Public Health Preparedness . 2016;10:274–280)